Students’ Perceptions Toward the Impact of English Movies on Students’ Vocabulary Knowledge - Maulida, Sarah; Warni, Silih (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
This study explores students' perceptions of the impact of watching English movies on vocabulary acquisition. The research involved interviews with seven 12th-grade students from one state high schools in Jakarta, focusing on their experiences with English movies and their effects on vocabulary acquisition. The findings reveal that watching English movies offers significant benefits for language learning, including vocabulary enrichment, contextual learning, and improved pronunciation and accent. Participants showed preferences for specific movie genres such as comedy, romance, and science fiction, which aligned with their interests and motivated them to continue engaging with English media for learning purposes. Despite encountering challenges such as understanding dialogues and accents, students found diverse exposure to language contexts beneficial for enhancing linguistic competence. Strategies such as using subtitles and note-taking were highlighted as effective methods for maximizing vocabulary learning. Overall, personal preferences in movie genres played a crucial role in motivating students and increasing enjoyment in the language learning process. This study provides insights into the positive impact of English movies on vocabulary acquisition and suggests practical strategies for incorporating movie-based learning approaches in language education.